The Effectiveness of Out-of-Class Learning Methods and Problem Solving Methods in Learning to Write Descriptive Texts for Grade VII Students of Junior High Schools/Islamic Junior High Schools - Faricha, Safira Maula; Kusmiatun, Ari (East Asian Journal of Multidisciplinary Research, 2025)
The purpose of this study is to determine the effectiveness of extracurricular learning methods and problem solving methods in learning to write explanatory essays of seventh grade students of SMP/MTS. This quasi-experimental study used a randomized pretest posttest control group research design. The population of this study consisted of only seventh grade students of MTsN 8 Blitar. The study sample consisted of students of seventh grade B as experimental group 1 and students of seventh grade E as experimental group 2. The results of the study showed that the significance value obtained for experimental group 1 was less than 0.05 (0.000 0.05). Ho was accepted and Ha was rejected. The mean post-test results of both methods showed that the use of extracurricular learning methods and problem solving methods had an impact on the results of students' explanatory essay writing.